The Institution of Nationality in the Context of Confessionalism - V. R. Atnashev (Евразийская интеграция: экономика, право, политика, 2019)
The paper considers main features of the Lebanese nationality (citizenship) and confessionalism that is central to the political system of Lebanon. The author proves that the confessionalism, complicated by clan relations in the Lebanese society leads to the state's loosening and to the dissolution of civil identity.